Competência midiática e informacional como ferramenta crítica na ciência da informação: estudo da desinformação e pós-verdade na série Black Mirror - Almeida, Rodrigo da Silva (2025)
The association between the disinformation industry and the social effects related to platformization - in addition to other trending phenomena, such as post-truth - results in an obstacle to people's informational autonomy. In this aspect, the study aims to identify elements associated with the current informational context and its relationship with Media and Information Literacy (MIL) represented in the film series Black Mirror. The elements of investigation are the phenomena of disinformation and post-truth and their underlying motivations and interests, and their relationships with the MIL dimensions. The research is classified as bibliographic and documentary, as the data comes from scientific literature, and excerpts from episodes of a film series are investigated. To analyze the collected data, we opted for content analysis of specific scenes from specific episodes of the series, which were selected based on their adherence to the theme of the investigated proposal, whose criteria are derived from the MIL dimensions idealized by Ferrés and Piscitelli (2015). The study made it possible to improve understanding of how information and communication technologies can shape the perception of reality, influence emotions, opinions and behaviors. It also reveals how false and distorted information can be used to manipulate public opinion, compromise democracy and individual privacy. Finally, it shows that MIL skills are essential for individuals in Latin America and the Caribbean in the contemporary era.